Tailoring Cognitive Task Analysis (CTA) Methods for Use in Healthcare. (September 2014) - Militello, Laura; Dominguez, Cindy; Ebright, Patricia; Moon, Brian; Russ, Alissa; Weir, Charlene
Cognitive task analysis (CTA) methods are most widely known for their contributions to military, nuclear power plant, and aviation research. In recent years, however, these methods have been adapted and applied with increasing frequency to address issues in healthcare. CTA methods have been used in the context of designing and integrating health information technology, in pursuit of improved patient safety, and as a means to improve education and training. This panel will 1) reflect on strategies for tailoring CTA methods for use in a range of healthcare settings, 2) highlight challenges to conducting CTA in healthcare settings, and 3) highlight important contributions of CTA in addressing challenging issues in healthcare today.